Social and Cultural Aspects of Russian Experimental Medicine During the Reign of Peter I - T. V. Kovaleva (Дискурс, 2019)
Introduction. The aim of the article is to show medicine as a multifaceted science influenced by social and cultural aspects that determine its structure and national features.Materials and methods. Historical, fiction and intellectual proses are chosen instruments of historical and literary discourses which determine its social and cultural aspects. The pathographic features of a medical discourse are taken from numerous examples of medical practices described in the fiction and scientific literature.Results. By focusing on the doctrine of double effect this study aims to show the historical path of Russian state medicine formation since the XVI century and understand it by modern approaches of the contemporary science, biomedical ethics.Discussion. One of the tasks is to show why modern medicine has such distinctive aspects and why Russian people demonstrate a specific attitude towards medicine and doctors. The special attention dedicated to one of the most popular Russian historical figures, Peter the Great, who had many skills and professions. The article shows him not only as a monarch, but also as a person with a keen interest in practical and experimental medicine, so he can be called an anatomist, surgeon, physician, dentist and intelligent collector.Conclusion. The work analyzes social and cultural aspects which influenced the state medicine formation according to Peter I vision.